51.6k views
3 votes
Find the inverse of f(x) = 6x - 3.

2 Answers

6 votes
F(x) is y so, y = 6x - 3.
Flip the equation around to get x= 1/6y + 1/2
User Jap Mul
by
5.5k points
3 votes

Answer:

f^-1(x)=x/6+1/2

Explanation:

f(x)=6x-3

Replace f(x) with y

Y=6x-3

Interchange the variable

X=6y-3

Rewrite the equation as

6y-3=x

Add 3 to both side

6y-3+3=x+3

6y=x+3

Divide each term by 6 and simplify

6y/6=x/6+3/6

Cancel the common factors

Y=x/6+1/2

Solve for Y and replace with f^-1(x)

f^-1(x)= x/6+1/2

User Delannoyk
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.